Appetite, eating and smoking habits: a study in Bragança - Almeida-de-Souza, Juliana (2015)
The literature indicates a strong relationship between smoking habits and food choices (Chatkin et al, 2007). We conducted a cross-sectional study with the aim of studing the relationship between smoking habits with appetite, consumption of coffee, alcohol, energy consumption, energy balance and macronutrient distribution. A questionnaire was sent to employees in the region of Bragança (Portugal), for institutional e-mail. It was questioned about their lifestyles, food intake through three days food recall, using photography to estimate the portion size. Each participant took photographs of all meals and beverages (one before and another after consumption) during two weeks and one weekend days. The portions size were estimate by dietitians and calculate the energy and macronutrients consumption and energy balance. The data were analyzed using SPSS trough Chi-square, Fisher’s Exact, Kruskal-Wallis and Mann-Whitney Tests. 129 individuals answered the questionnaire, but only 20 participated in the photographic food recall. It was found that 20% were smokers with an average caloric intake of 2192.2 ± 317.4 kcal, 60% of non-smokers with 2168.6 ± 635.4 kcal and 20% of ex-smokers with 2166.9 ± 292.5 kcal. It was found an association between smoking habits and coffee consumption (p = 0.020, Phi = 0.206), alcohol (p = 0.005, Phi = 0.250) and appetite (p = 0.028). No association was found between smoking habits and total energy, energy balance and macronutrient distribution. Dietary intake and macronutrient distribution were not related to the smoking habits. However, it was found a weak association between coffee and alcohol consumption and smoking habits. Also, it was found that ex-smokers have increased appetite.